Ubiquitin-dependent translation control mechanisms: Degradation and beyond - Pierce W. Ford; Mythreyi Narasimhan; Eric J. Bennett (Cell Reports)
Summary: Translation control mechanisms connect the largely static genome to the highly dynamic proteome. At each step in the translation cycle, multiple layers of regulation enable efficient protein biogenesis under optimal conditions and mediate responses to acute environmental challenges. Recent research has demonstrated that individual ribosomal protein ubiquitylation events act as molecular signals to specify quality control pathway outcomes. Here, we synthesize current knowledge of ubiquitin-mediated translation control mechanisms and highlight key outstanding questions. We compare and contrast ubiquitin-dependent mechanisms that regulate ribosome-associated quality control pathways at several steps in the translation cycle. We also explore how distinct ribosome ubiquitylation events on specific ribosomal proteins impact translation activity and how defects in specific ubiquitin-mediated regulatory steps impact physiology and health.